The Effect of Transformational Leadership and Goal Clarity on Employee Performance - Adebowale I. O.; Maiza Fikri (West Science Business and Management, 2026)
Employee performance is a crucial factor that determines organizational effectiveness and competitiveness. Organizations increasingly rely on effective leadership and clear organizational goals to improve employee productivity and work outcomes. This study aims to examine the effect of transformational leadership and goal clarity on employee performance in Indonesia. The research adopts a quantitative approach using a survey method. Data were collected from 150 employees working in various organizations in Indonesia through a structured questionnaire measured using a five-point Likert scale. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25, employing descriptive statistics, validity and reliability testing, and multiple regression analysis. The results indicate that transformational leadership has a positive and significant effect on employee performance, suggesting that leaders who inspire, motivate, and provide a clear vision contribute to improved employee productivity and engagement. In addition, goal clarity also shows a significant positive effect on employee performance, indicating that employees perform better when organizational goals and expectations are clearly communicated. Furthermore, the simultaneous analysis reveals that transformational leadership and goal clarity together significantly influence employee performance, with a coefficient of determination of 50.7%, indicating that these variables substantially contribute to explaining employee performance. The findings highlight the importance of effective leadership practices and clear goal-setting in enhancing employee outcomes. This study contributes to the literature on organizational behavior and human resource management by providing empirical evidence from the Indonesian context and offers practical implications for managers seeking to improve employee performance through leadership development and clear communication of organizational goals.